PROBING-PROMPTING LEARNING: ITS EFFECT ON IMPROVING CONCEPTUAL UNDERSTANDING IN MATHEMATICS - Hanifa, Ulfa; Suhendra, Suhendra; Jauhari, Muhammad Fakhri (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Understanding mathematical concepts plays a crucial role in students achieving favorable learning outcomes. However, there remains room for improvement in students' grasp of these concepts. The main objective of this research was to assess how effective the probing prompting learning model is in improving students' understanding of mathematical concepts. This research employed the quantitative approach with the experimental method. Used tests, observations, and questionnaires to collect the data. The study included 25 students in the experimental group and 26 students in the control group. The findings showed: 1) The average percentage of teacher activity was 96.30% (“very good” category); 2) The t-test analysis findings showed a significant difference in the enhancement of understanding of mathematical concepts between students exposed to the probing prompting learning model (high category) and those using conventional learning approach; 3) Students responded positively to the probing prompting learning model, as evidenced by their attitude. In conclusion, this study suggests that the probing prompting learning model can serve as an effective alternative for facilitating learning and improving students' understanding of mathematical concepts.